Coral reef mesopredators switch prey, shortening food chains, in response to habitat degradation. Issue 8 (18th March 2017) - Hempson, Tessa N.; Graham, Nicholas A. J.; MacNeil, M. Aaron; Williamson, David H.; Jones, Geoffrey P.; Almany, Glenn R.
Abstract: Diet specificity is likely to be the key predictor of a predator's vulnerability to changing habitat and prey conditions. Understanding the degree to which predatory coral reef fishes adjust or maintain prey choice, in response to declines in coral cover and changes in prey availability, is critical for predicting how they may respond to reef habitat degradation. Here, we use stable isotope analyses to characterize the trophic structure of predator–prey interactions on coral reefs of the Keppel Island Group on the southern Great Barrier Reef, Australia. These reefs, previously typified by exceptionally high coral cover, have recently lost much of their coral cover due to coral bleaching and frequent inundation by sediment‐laden, freshwater flood plumes associated with increased rainfall patterns. Long‐term monitoring of these reefs demonstrates that, as coral cover declined, there has been a decrease in prey biomass, and a shift in dominant prey species from pelagic plankton‐feeding damselfishes to territorial benthic algal‐feeding damselfishes, resulting in differences in the principal carbon pathways in the food web. Using isotopes, we tested whether this changing prey availability could be detected in the diet of a mesopredator (coral grouper, Plectropomus maculatus ). The δ 13 C signature in grouper tissue in the Keppel Islands shifted from a more pelagic to a more benthic signal, demonstrating a change in carbon sources aligning with the change in prey availability due to habitat degradation. Grouper with a more benthic carbon signature were also feeding at a lower trophic level, indicating a shortening in food chains. Further, we found a decline in the coral grouper population accompanying a decrease in total available prey biomass. Thus, while the ability to adapt diets could ameliorate the short‐term impacts of habitat degradation on mesopredators, long‐term effects may negatively impact mesopredator populations and alter the trophic structure of coral reef food webs. Abstract : Coral reef habitats throughout the world are facing extensive degradation, which is hypothesised to result in a loss of predators and shortened food chains, yet we lack empirical evidence of these altered trophodynamics. This study asks whether a mesopredator in a complex coral reef foodweb can change its' trophic niche to adapt to altered prey availability. Using stable isotope analyses, we show that coral grouper can alter their prey source in response to a modified foodweb associated with coral habitat decline, and that their trophic position decreases following disturbance, indicating a shortened food chain. Photo credit: M.V. Kitahara